ASSESMENT OF CORRELATION IMPACT OF DEFICIENT INTAKE OF RDA ON HEALTH - Sonkar , Seema; Gupta, Sunaina (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
This study is conducted for the information collected by survey represented the different intake of nutrients in respondents male and female. The survey value compared with RDA value and found deficient percent and increment energy value found that 1418.4 deficient in males and 1081.2 in females whereas, the protein intake value compared with RDA 16.7 percent increment found in males and 20.8 in females. Calcium intake value compared with RDA 415.5 increment in males and 383.8 found in females. Iron intake value compared with RDA 2.89 increment in males and 11.8 deficiency found in females. B1 intake value compared with RDA 0.74 increment in males and 1.31 deficiency found in females. C intake value compared with RDA 25.3 deficient in males and 37.6 found in females. An intake value compared with RDA 755.5 deficient in males and 63.9 found in females. They take a large amount of energy and fat. After all, they consume more fast food and rice because they easily make and take less time to cook. Vitamins deficient like vitamin A and C vitamins because they consume less fruit. After all, fruits are costly. Vitamin B1 and B2 found increment because they consumed whole grain foods like rice, and fast foods are cheaply easily locally available food.